Effects of rotigotine transdermal system on non-motor symptoms in Parkinson's disease: an overview. (December 2013) - Zesiewicz, Theresa A; Martinez-Martin, Pablo
Parkinson's disease (PD) is a progressive neurodegenerative disease, involving the dopaminergic, noradrenergic, serotonergic and cholinergic systems. In addition to its cardinal motor symptoms, PD is associated with a diverse range of non-motor symptoms (NMS) that may be more important than motor symptoms. Although there is evidence for a dopaminergic contribution for several NMS in PD, NMS have been underrecognized and undertreated by clinicians. There is evidence that dopaminergic therapy, including dopamine agonists, may alleviate some NMS, such as anxiety and depression. This review focuses on published data on the effects of the non-ergoline dopaminergic agonist rotigotine transdermal system in the treatment of NMS in patients with PD. Data on the effects of orally administered non-ergoline agonists, including ropinirole and pramipexole, on NMS are also summarized.